Océans, Cosmos, Antarctique : de nouveaux espaces de conquête? - Pic, Pauline; Lasserre, Frédéric (Société d'études historiques des relations internationales contemporaines, etc., 2020)
Oceans, especially in polar regions but also the outer space, are considered today as the “last frontiers”. These spaces where States project power are also spaces where States face several specific challenges, which are notably of an environmental nature. They invite us to rethink the modes of political action. How, then, do States deal with these non-traditional spaces, and how do they structure their action there? In this paper, through several concrete examples, we seek to initiate a process of reflection by highlighting certain logics that underlie the organization of international political action in these spaces. We question their nature and what it implies in terms of “conquest”. The international community has managed to frame potential appetites in international conventions. But if legal frameworks do exist, that does not mean that they have the capacity to appease all the tensions created by the desire to control these spaces. The questions raised by current events also highlight complex issues of a different nature, sometimes relating to sovereignty (as in Antarctica, for example), whilst at times relating to sovereign rights, when we speak of extended continental shelves, or the right to place satellites in orbit… These questions also gain a new dimension in connection with the presence of new players, whether state or private. How do these actors envisage these non-traditional spaces? On considère aujourd’hui les océans – et notamment les océans polaires – mais aussi l’espace, comme les « dernières frontières ». Ces espaces de projection de puissance pour certains États sont également porteurs d’enjeux particuliers, environnementaux notamment, qui invitent à repenser les modes d’action politique. Comment les États font-ils face à ces espaces non traditionnels, et comment y structurent-ils leur action ? Nous proposons dans cet article, à travers plusieurs exemples concrets, d’entamer la réflexion en mettant en relief certaines logiques qui sous-tendent l’organisation de l’action politique ...